I Make Them Ready: “A Study on Lecturer’s Consistency of Teaching Technique in Preparing Prospective English Teacher” - Nina Desmita (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: This study aimed to discover the reasons for the lecturer’s consistency to use a particular teaching technique which is a discussion technique with an unusual system for preparing prospective English teachers. The Qualitative data were collected by semi-structured interviews through a case study as the research design. The data showed that the demographic condition, providing the environment to create active participation and improving students’ language skills were the reasons for the lecturer consistency of teaching technique. From the findings, it can be concluded that not the variance of teaching technique can decide students’ quality but providing the most appropriate teaching technique based on students’ needs was the key to help students based on their needs. Abstrak: Penelitian ini bertujuan untuk menemukan alasan konsistensi dosen untuk menggunakan teknik pengajaran tertentu yang merupakan teknik diskusi dengan sistem yang tidak biasa untuk mempersiapkan calon guru bahasa Inggris. Data kualitatif dikumpulkan dengan wawancara semi-terstruktur melalui studi kasus sebagai desain penelitian. Data menunjukkan bahwa kondisi demografis, menyediakan lingkungan untuk menciptakan partisipasi aktif dan meningkatkan keterampilan bahasa siswa adalah alasan konsistensi dosen teknik pengajaran. Dari temuan, dapat disimpulkan bahwa bukan varian teknik pengajaran yang dapat menentukan kualitas siswa tetapi memberikan teknik pengajaran yang paling tepat berdasarkan kebutuhan siswa adalah kunci untuk membantu siswa berdasarkan kebutuhan mereka.